(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 1988)
This article analyses the discourse of Un mundo para Julius (1971) based on specific theoretic concepts developed by M. Bakhtin, especially those from “Discourse in the novel” (1934). That is how the different strategies used by the author, Alfredo Bryce Echenique in order to build a parodic picture of the “limeña” society will be exposed and understood.